2016
DOI: 10.1016/j.acra.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Solid Breast Lesions in 2D Shear Wave Elastography is an Indicator of Malignancy

Abstract: Rationale and Objectives: To investigate if anisotropy at 2D Shear Wave Elastography (SWE) suggests malignancy and whether it correlates with prognostic and predictive factors in breast cancer. Materials and Methods: Study-group A of 244 solid breast lesions was imaged with SWE between April 2013 and May 2014. Each lesion was imaged in radial and anti-radial planes and the maximum elasticity Emax, mean elasticity Emean and standard deviation SD were recorded and correlated with benign/malignant status and if m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
1
25
1
Order By: Relevance
“…However, ROI size should be considered when interpreting the results of E mean . Because E mean is the sum of all elasticity values of each pixel within the ROI divided by the number of pixels, its absolute value depends on the size of the ROI; that is, a higher E mean value for a smaller ROI is expected [ 28 ]. E SD , representing the average difference in elasticity value within the ROI to E mean , is also influenced by the ROI size [ 28 ].…”
Section: Image and Data Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ROI size should be considered when interpreting the results of E mean . Because E mean is the sum of all elasticity values of each pixel within the ROI divided by the number of pixels, its absolute value depends on the size of the ROI; that is, a higher E mean value for a smaller ROI is expected [ 28 ]. E SD , representing the average difference in elasticity value within the ROI to E mean , is also influenced by the ROI size [ 28 ].…”
Section: Image and Data Interpretationmentioning
confidence: 99%
“…Because E mean is the sum of all elasticity values of each pixel within the ROI divided by the number of pixels, its absolute value depends on the size of the ROI; that is, a higher E mean value for a smaller ROI is expected [ 28 ]. E SD , representing the average difference in elasticity value within the ROI to E mean , is also influenced by the ROI size [ 28 ]. As the size of the ROI changes, the sampling of the elasticity information becomes more variable, meaning that elastic heterogeneity will increase or decrease, particularly in a heterogeneous malignant lesion.…”
Section: Image and Data Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative information is also provided via the generation of a tissue stiffness map. USWE has been shown to be useful for assessing liver fibrosis, and predicting malignancy risk in thyroid nodules or discrete breast lesions. Sowa et al .…”
Section: Quantifying Fibrosismentioning
confidence: 99%
“…Recently, Zhou et al has demonstrated the anisotropy of elasticity of normal breast glandular and fatty tissue by comparing measurements of radial and antiradial planes [ 13 ]. Previous studies observed anisotropy in solid breast lesions [ 14 ], and Skerl et al discovered anisotropy in SWE as an indicator of malignancy [ 15 ]. Nevertheless, in the aforementioned study, the anisotropy factor (AF) was calculated with Emean, which was defined as mean elasticity of the stiffest area using a region of interest size (ROI) of 2 mm, rather than the measurements of the whole lesions.…”
Section: Introductionmentioning
confidence: 99%